Does group engagement with members constitute a “beneficial inefficiency”? - Grömping, Max; Halpin, Darren (Governance, 2019)
This article explores the role of variations in organizational form in explaining levels of group access. Specifically, we test whether group forms incorporating more extensive engagement with members receive policy advantages. We develop and test a account of beneficial inefficiencies. Our account reasons that the costs of inefficient intraorganizational processes and practices associated with enhanced engagement with members are beneficial as they generate crucial “access goods”—specifically encompassing positions—that in turn receive enhanced policy benefits. The costs of intraorganizational practices allowing members to engage more thoroughly in decision making are thus beneficial inefficiencies. We test this proposition using data on the Australian interest group system. Using the tools of cluster analysis, we identify three forms, each varying in respect of the inefficiencies they embody. Our multivariate analysis finds strong support for the account of beneficial inefficiencies: groups with the most inefficient organizational model receiving the greatest policy access.